Error Analysis of Students’ English Pronunciation in Reading Aloud at Universitas Hindu Indonesia - Yeni Yuliantari; Ida Bagus Made Sadu Gunawan; Ni Putu Ayu Kusumawati (Journal of Language and Applied Linguistics, 2026)
This study aims to analyze students’ English pronunciation errors in reading aloud at Universitas Hindu Indonesia. It focuses on identifying the types of errors and examining the factors contributing to them. This research employs a descriptive qualitative design involving 12 first-semester students selected through purposive sampling. Data were collected through reading-aloud tasks, classroom observations, and semi-structured interviews. The reading performances were audio-recorded and analyzed using English phonology and Error Analysis frameworks, while the interview data were analyzed using thematic analysis. Data triangulation was applied to enhance the credibility of the findings. The results identified a total of 59 pronunciation errors, comprising 29 consonant errors (49.1%), 26 vowel errors (44.1%), and 4 stress errors (6.8%). Thematic analysis of the interview data revealed five factors contributing to pronunciation errors: first language interference, lack of pronunciation practice, limited exposure to English, low confidence, and poor phonological awareness. These factors were consistently supported by classroom observations and pronunciation recordings. These results suggest that pronunciation remains a significant challenge for EFL students. Therefore, greater emphasis on pronunciation practice and increased exposure to authentic English are recommended to improve students’ speaking proficiency.